Anti-corruption, criminological and legal expertises of normative legal acts (comparative analysis) - E. I. Yulegina (Russian Journal of Economics and Law)
Objective: to determine whether anti-corruption expertise is an independent kind of expertise of normative legal acts or belongs to some type of expertise of normative legal acts. On the basis of the conducted analysis, to formulate a definition of anti-corruption expertise. Methods: comparative-legal method of research. Results: On the basis of the conducted analysis of the similar and different features of criminological, legal and anti-corruption expertise, the anti-corruption expertise is defined, according to which anti-corruption expertise is a form of criminological examination which uses the methods of legal expertise. Scientific novelty: In the article for the first time the legal, anti-corruption and criminological expertise is systematically analyzed as the expertise of normative legal acts according to the following criteria: subject, object, method, purpose, provisions for the mandatory examination, recording of results. It was found that the specification of expertise regulations should be carried out according to the criterion "the purpose of expertise”. The study allowed to identify the features of criminological and legal expertise in anti-corruption expertise of normative legal acts. Practical value: The formulated theoretical determination of anti-corruption expertise as a synthesis of criminological and the legal expertise allows to use the existing theoretical and practical experience of organizing and conducting criminological and legal expertise to improve the organization and conduct of anti-corruption expertise. The theoretical provisions can be used in scientific, legislative and enforcement activities, in the educational process of higher educational institutions of legal profile for improving the skills of practitioners and scientific-pedagogical personnel in the sphere of combating corruption.